Penggunaan Rasch Model dalam Menganalisis Butir Soal Matematika Kelas V Sekolah Dasar - Aqida, Debbi Silvia (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research is motivated by the large number of test equipment used in schools and the quality of the questions is unknown. Therefore, the assessment results may be false or not reflect the students’ true abilities. This research was conducted to analyze the questions used to measure the suitability of the questions and the level of difficulty of the questions for class V students in mathematics at Pekalongan Private Elementary Schools. The research method used is evaluation with a quantitative descriptive approach. The Rasch model is used to obtain fit test items. This analysis was carried out with the help of Winsteps software. From the output of the Winsteps program, the results obtained were 15 questions according to the Rasch model with an Outfit MNSQ value of 1.03. Meanwhile, the Outfit ZSTD value is 0.0. As well as the PT-measure Corr which has a positive value, there are 11 questions and 4 questions have a negative value. This means that there are 4 questions that do not fit the model. The results of the research show that the mathematics assessment questions can meet at least one of the three predetermined criteria and are in accordance with the fit characteristics. On the other hand, one question is considered easy based on the difficulty level of the question.